Influence of tillage and nutrient management strategies on rice (Oryza sativa L.) productivity, nutrient uptake and soil properties - Kumar, Pittala Manoj; Roy, Dhirendra Kumar; Ranjan, Shivani; Sow, Sumit (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted during 2019 to study the effect of tillage and nutrient management strategies on rice productivity, nutrient uptake and soil properties in Eastern Indo Gangetic Plains (EIGP) of India. The experiment was laid out in split-plot design with three replications. Nine treatment combinations comprising of three tillage methods in the main plots viz., Conventional tillage, Zero tillage and Zero tillage + Residue management and three nutrient management practices viz., recommended dose of fertilizer (RDF), SSNM based on Nutrient expert and 60 % RDN + green seeker guided N application (GSGN) + 100% RDP + 100% RDK in the subplot. The results of the study revealed that residue management with zero tillage practice resulted in 14.03 % and 9.27 % higher grain and straw yield than conventional tillage respectively. Zero tillage with residue management increased nutrient uptake to the maximum of 86.71 kg N, 24.62 kg P and 99.99 kg K/ha as compared to conventional tillage. Among nutrient management, SSNM based on Nutrient expert exhibited the highest grain (4.5 t/ha ) and straw yields (6.4 t/ha ), while 60 % RDN+ GSGN + 100% RDP + 100% RDK showed at par of these values. Adoption of SSNM based on Nutrient expert resulted in maximum N, P and K uptake. Different tillage and nutrient management regimes did not affect the soil properties significantly. Thus, zero tillage and residue management with SSNM based on Nutrient expert is a viable management practice for improving productivity under DSR in EIGP of India.